Clinical symptom clusters, neurocognitive function, balance and vestibulo-ocular function in athletes with sport-related concussion - Claus Reinsberger; Lea Weike; Rebecca Reeschke (BMJ Open Sport & Exercise Medicine)
Objective This cross-sectional study aimed to investigate subjective and objective deficits of neurocognitive function, balance and vestibulo-ocular performance in athletes with sport-related concussion (SRC) compared with healthy control athletes.Methods 72 patients with SRC and 72 matched healthy controls were included. All participants performed computerised testing of neurocognitive function, device-assisted balance testing and objective evaluation of vestibulo-ocular function (video head impulse and dynamic visual acuity test). Clinical symptom clusters (headache/migraine, anxiety/mood, fatigue, cognitive, vestibular, ocular) were determined for each patient using the Sport Concussion Assessment Tool, 5th edition symptom evaluation. Independent t-tests or Mann-Whitney U tests were calculated to test for group differences in the whole cohort and according to clinical symptom clusters.Results When investigating the whole cohort, significant differences between patients with SRC and control subjects were found in one parameter of balance testing (sway velocity double-firm), with lower performance in the SRC group (p<0.001, r=0.345). The number of symptom clusters assigned to the SRC patients ranged from 0 (no definite cluster) to 6 (all clusters), and all clusters were frequent in the investigated cohort. Patients with vestibular, cognitive and fatigue symptom clusters demonstrated significantly lower performance in balance testing compared with SRC patients without those clusters (p<0.001 to p=0.005, r=0.368–0.439). Additionally, SRC patients presenting with symptoms of the fatigue cluster demonstrated significantly worse performance in vestibulo-ocular testing compared with SRC patients without the fatigue cluster (p=0.006, d=0.781).Conclusion SRC patients presented with variable numbers and qualities of clinical symptom clusters. Some subjective clusters were associated with abnormal objective tests of other clusters (vestibular, cognitive and fatigue with abnormal balance; and fatigue with abnormal vestibulo-ocular performance). Clinical symptom clusters and their overlap should be considered when examining patients with SRC.